PENGARUH GAYA HIDUP KONSUMTIF, FITUR DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE - Desti Dirnaeni; Suwardi Suwardi; Aditya Rian Ramadhan; Perli Iswanto (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
Technology that is growing and the number of people's demands for ease of transactions makes businessmen in the smartphone industry try to meet the needs of their prospective customers. Of course, the resulting smartphone products not only function as a means of communication but can also make payment transactions and even fashion. The purpose of this study was to determine the effect of consumptive lifestyle, features and sales promotions on purchasing decisions both partially and simultaneously. The iPhone smartphone is used as an object in this study and the subject is people who live in Bekasi City who have not used an iPhone. The analytical tool used is multiple linear regression test, partial test and simultaneous test. Based on the results that have been obtained, it can be seen that partially and simultaneously consumptive lifestyles, features and sales promotions affect purchasing decisions for Iphone smartphones